MicroRNA-126 Priming Enhances Functions of Endothelial Progenitor Cells under Physiological and Hypoxic Conditions and Their Therapeutic Efficacy in Cerebral Ischemic Damage - Qunwen Pan; Jieyi Zheng; Donghui Du; Xiaorong Liao; Chunlian Ma; Yi Yang; Yanyu Chen; Wangtao Zhong; Xiaotang Ma (Stem Cells International)
Endothelial progenitor cells (EPCs) have shown the potential for treating ischemic stroke (IS), while microRNA-126 (miR-126) is reported to have beneficial effects on endothelial function and angiogenesis. In this study, we investigated the effects of miR-126 overexpression on EPCs and explore the efficacy of miR-126-primed EPCs (EPCmiR-126) in treating IS. The effects of miR-126 overexpression on EPC proliferation, migratory, tube formation capacity, reactive oxygen species (ROS) production, and nitric oxide (NO) generation were determined. In in vivo study, the effects of EPCmiR-126 on the cerebral blood flow (CBF), neurological deficit score (NDS), infarct volume, cerebral microvascular density (cMVD), and angiogenesis were determined. Moreover, the levels of circulating EPCs (cEPCs) and their contained miR-126 were measured. We found (1) miR-126 overexpression promoted the proliferation, migration, and tube formation abilities of EPCs; decreased ROS; and increased NO production of EPCs via activation of PI3K/Akt/eNOS pathway; (2) EPCmiR-126 was more effective than EPCs in attenuating infarct volume and NDS and enhancing cMVD, CBF, and angiogenesis; and (3) infusion of EPCmiR-126 increased the number and the level of miR-126 in cEPCs. Our data indicate that miR-126 overexpression enhanced the function of EPCs in vitro and in vivo.